2022
DOI: 10.3390/vaccines10050681
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Acceptance of COVID-19 Vaccines in a Country with a High Vaccination Rate

Abstract: Control of the COVID-19 pandemic largely depends on the effectiveness of the vaccination process. An understanding of the factors that underlie the willingness to accept vaccination contributes pivotal information to controlling the pandemic. We analyzed the association between the willingness to accept the available COVID-19 vaccines and vaccine determinants amidst the Chilean vaccination process. Individual-level survey data was collected from 744 nationally representative respondents and multivariate regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
(59 reference statements)
3
22
0
1
Order By: Relevance
“…Most of those variables were chosen based on previous research identifying them as factors associated with COVID-19 vaccine hesitancy. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A few (personality traits, work-life-balance, satisfaction with work, self-reported type in conversations) were included based on a priori hypotheses by the research team, related in part to our previous study of vaccine hesitancy in Austria. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of those variables were chosen based on previous research identifying them as factors associated with COVID-19 vaccine hesitancy. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A few (personality traits, work-life-balance, satisfaction with work, self-reported type in conversations) were included based on a priori hypotheses by the research team, related in part to our previous study of vaccine hesitancy in Austria. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%
“…27 , 28 Another previous study reported that acceptance of an annual COVID-19 vaccine decreased with increasing trust in religious leaders. 23 Therefore we hypothesized that more frequent participation in religious meetings would be associated with lower willingness to receive an annual COVID-19 booster in our sample.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations